Kebijakan Penerapan Pembatasan Sosial Berskala Besar: Analisis Tekstual pada akun instagram @IDNTimes - Arika Bagus Perdana; Virginia Ayu Sagita (Jurnal Paradigma, 2021)
The government first implemented the PSBB from April 10, 2020, to April 24, 2020. This PSBB applies to the DKI Jakarta area and its surroundings included in the high-risk distribution. However, the PSBB regulations are considered less effective. This can be seen from the number of Covid-19 cases that are increasing every day. The public can access information about PSBB from various media. Based on the existing data, there are more social media users than other digital media such as the data above. The methodology used in this research is descriptive qualitative textual analysis. This textual analysis aims to identify texts related to the news context. Data collection is done by collecting news on the @IDNTimes Instagram account from April 2020 to June 2020. In the @IDNTimes Instagram post about the PSBB regulations, there are news writing objectives, target audience, writing techniques, and news context. The context of the news on the @IDNTimes Instagram post is still related to the Covid-19 pandemic.